QUANTITATIVE DETERMINATION OF SOME NON-STEROIDAL ANTI-INFLAMMATORY DRUGSAND THEIR ACID DISSOCIATION CONSTANTS BY DIRECT POTENTIOMETRY - MASLARSKA, VANIA (International Journal of Applied Pharmaceutics, 2024)
Objective: A potentiometric titration method was applied to determine non-steroidal anti-inflammatory drugs. The quantitative analysis and the treatment of the primary data are based on a nonlinear regression procedure using commercial software. A general formula valid for every type of acid-base titration, derived before is used as a direct input. Methods: Potentiometric titration of ibuprofen, flurbiprofen, and ketoprofen with sodium hydroxide solution (0.1 mol/l). The solutions of ibuprofen, flurbiprofen, and ketoprofen were prepared in solvent CH3OH: H2O (40:60%). The determination was carried out using a 713 Metrohm pH meter, equipped with Metrohm combined electrode ref. 6.0228.000 Pt1000 with temperature sensor and auto burette. The analysis was performed at ionic strength (I=0.2 mol/l KCl) and t = 25±0.2 °C. Results: The discussed substances were analyzed using potentiometric titration with a standard sodium hydroxide solution (0.1 mol/l). The experimental data V, ml/E, mV and the conditions of these titrations were used as input in the Data Fit program fixing the following parameters Vo =100.0 ml; Ct (NaOH) = 0.1000 mol/l; S = 59.16 mV (corresponding to 25 °C theoretical value) and Kw = 1.2 10-14 (ionic strength 0.2 mol/l). The analytical results for ibuprofen, flurbiprofen and ketoprofen were determined with good accuracy (error+0.4 % foribuprofen+0.2 % for flurbiprofen and+0.2 % for ketoprofen) and precision (1 % for the three). The quantity and acid-base constants of ibuprofen, flurbiprofen, and ketoprofen were determined alone and in tablets. The validation of the method showed very good accuracy and precision. Conclusion: The present approach can be successfully used in routine analysis of the study drugs in quality control laboratories.